Recovering the Multiple Worlds of the Medieval Church: Thoughtful Lives, Inspired Critics, and Changing Narratives - Van Engen, John (The catholic historical review, 2018)
The author reflects on his scholarship in Medieval Church history at the University of Notre Dame. Topics covered include churches during his childhood in rural southwest Iowa, the need for scholars to consider rural peasants whose labor fed clergy and lords, significance of Medieval Latin to his intellectual life, and response to his essay on Christian Middle Ages.